The Effect of Social Networks on the Economic Outcomes of a Disadvantaged Group: Evidence from Tribal Affiliations - Isabelle Sin; Steven Stillman (Institute of Labor Economics (IZA), 2017)
Minority groups in many countries, particularly indigenous populations, live in very segregated environments. Many social scientists believe that social networks create poverty traps in these types of segregated environments, with a lack of positive role models reinforcing a lack of good job opportunities. In this paper, we use data from the New Zealand Census to examine the relationship between the strength of an individual's local social network and their labor market outcomes. We focus on outcomes for Māori, which allows us to use tribes as exogenously formed networks, and traditional tribal ties to specific geographical regions as an exogenous shock to the locations of social networks. We thus avoid the typical problem of endogenously formed networks and network locations. We find that Māori who locate in areas with strong networks have modestly worse labour market outcomes than Māori from other tribes in the same areas. However, when we account for the endogenous selection of Māori into high networks areas, we find that they are negatively selected on both observables and unobservables and that social networks have a positive causal impact on employment and total income for women and wage rates for men. These results are consistent with those found in the literature on immigrant enclaves and allude to role that social networks play in improving job match quality.
Keywords: J61; J15; R23; 330; labour market outcomes; mobility; social networks; New Zealand; Māori